Epistemological implications of Complex Thought for the conformation of a Semiotics of Culture - Brower Beltramin, Jorge (Estudios de Filosofía, 2008)
The objective of this article is to develop a set of reflections of a theoretico-espitemological character on the complex thought of E. Morin, which finally serve as a support for the proposal of a Semiotics of Culture in which the fundamental principles of this thought and its direct conceptual implications are integrated. With this aim in mind we review here the theoretical device proposed by Morin, so as to establish the basic methodological lineaments or analytical instances on which to define the Semiotics of Culture. Finally we can indicate that the present work represents an attempt at systematization of a transdisciplinary conceptual battery whose gnoseological power makes possible the bettering of methodologies of analysis such as the Semiotic on specific Systems of Meaning.